Factors Related to Overnutrition in Early Childhood in Urban and Rural Areas of Bangka Belitung Islands Province (An Analysis Of 2023 SKI Data) - Harahap, Afifa Naura; Hikmayani, Nur Hafidha; Sumardiyono, Sumardiyono (Media Publikasi Cendekia Indonesia, 2025)
Early childhood is a critical period for the basic development of physical, social, and cognitive aspects. One of the nutritional problems that often occurs is overnutrition. This study aims to determine the factors of gender, history of birth weight, history of breastfeeding, and consumption of formula milk related to the incidence of overnutrition in early childhood in urban and rural areas. This study uses secondary data from the 2023 SKI data. The design of this study is a cross-sectional study, a population of children aged 0-24 months with a sample size of 417 children. Univariate data analysis, a Chi-square test to explore differences in place of residence in overnutrition status, and bivariate (logistic regression) with the help of Stata software version 17. The results show that 7.26% of early childhood children who experience overnutrition live in rural areas, and 6.83% live in urban areas. There was no significant association between male gender (OR=0.99, 95% CI=0.40–2.46), history of risky birth weight (OR=1.00, 95% CI=0.54–3.28), non-exclusive breastfeeding (OR=1.16, 95% CI=0.40–3.31), or consumption of formula milk (OR=1.32, 95% CI=0.46–3.79) in urban areas with overnutrition (p>0.05). There was no significant association between male gender (OR=0.99, 95% CI=0.25–3.90), history of high-risk birth weight (OR=1.00, 95% CI=0.99–1.00), non-exclusive breastfeeding (OR=0.77, 95% CI=0.15–3.92), or formula milk consumption (OR=0.84, 95% CI=0.16–4.31) in rural areas with overnutrition (p>0.05). These findings suggest that although gender, history of birth weight, history of breastfeeding, and consumption of formula milk were not significantly associated with overnutrition in early childhood, interventions should focus on structural determinants such as maternal education and access to exclusive breastfeeding support, especially in rural communities.